Development of Poster-Based Learning Media in the Information and Communication Technology Subject at State Middle School 1 BPR Ranau Tengah - Novita Sari K; Supandi Supandi; Ade Ricky Rozzakya Rozzakya; Wijayanto Wijayanto (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to develop poster-based learning media for Information and Communication Technology subjects at SMP 1 BPR Ranau Tengah to improve student motivation and understanding. This study uses the Research and Development (R&D or RnD) method to develop poster-based learning media. This development research uses the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model, which includes the stages of analysis, design, development, implementation, and evaluation. The focus of this study includes the process of identifying learning needs in the classroom, developing media that suits those needs, and analyzing the effectiveness of its use in improving student understanding. This research was conducted at SMP Negeri 1 BPR Ranau Tengah. Data collection techniques in this study used observation and semi-structured interviews. The data obtained were then analyzed descriptively qualitatively. The results of the study indicate that the development of poster media at SMP Negeri 1 BPR Ranau Tengah proved to be effective. The developed poster media successfully achieved the stated objectives of increasing knowledge, changing attitudes, increasing participation, and improving students' understanding in Information and Communication Technology lessons. As some students have better understood the poster media effectively and have achieved the goal of presenting Information and Communication Technology information visually, helping students understand abstract concepts such as computers and internet networks. Teachers' creative designs and the use of graphic design technology increase learning interest and flexibility of use, both inside and outside the classroom, and can be an example for innovative Information and Communication Technology learning.